(untitled) (Agora for Physical Education and Sport, 2022)
How to develop critical Physical Education? How to address social and epochal change in the classroom? Why is it necessary to create tools with critical pedagogies? “Physical Education as a tool for social transformation. Critical pretexts” is a book published by the Seminar of Critical Physical Education Soca-rel, a space made up of teachers from different educational stages in the Teacher Training Faculty of the University of Valencia. Faced with the need for Physical Education to rethink itself and develop new modes of representation, inclusion, and visibility, the aim is to denormalize the traditional conception of the discipline through proposals with which to redirect toward reflection and criticism, provoking, dialoguing, and embracing the postulates of transformative practice in order to provide full educational arguments and position itself with legitimacy in the contemporary pedagogical field.